Flexural Behavior of Reinforced Concrete Beams layers with Silica Fume and Steel Fiber - Manal kademAbdullah; Dr. Ali k. Al-Asadi (Genius Journals, 2022)
In this paper study, Nine beam samples with measurements of 1150 x 200 x 120 mm were prepared to examine the bending behavior of reinforced concrete (SRC,SRFC and SFRCH) beams exposed to flexural .All tested beams have the same rectangular section (W x H) of 1150 x 200mm. The span of the beams is 1000mm . Two ∅10 mm longitudinal reinforced have been provided at top and bottom. In addition, stirrups reinforcement of ∅10@50mm have been added to assure a pure flexural failure. Steel reinforcement has been designed and provided to allow the beams to fail under reinforcement failure scenario.. Letters S , F, SP “N.C,” “SRC,SFRC and SFRCH refer to the silica fume ,steel fiber, Superplaciticizer ,normal control, beams with silica fume ,steel fiber and beam with layers respectively. silica and steel fiber were added to form S8F1 beam as a layers with thickness (H) corresponding to 1.5cm ,3cm, 6cm, 9cm, 12cm and 20cm. Figure 4-1 shown the beam specimens used as layers .Table 3 shows the proportion of concrete mix of the current study. For the lowest layer of C35 grade concrete in this investigation, we utilized concrete mixtures with 8% silica fume and 1% steel fiber, and for the upper layer, we used concrete mixtures with 8% silica fume and 0% steel fiber. The ideal thickness of the beam layers was S8F0H12, which improved the outcomes of the ultimate state as the thickness of the SFRCH layer increased. Given that S8F0H6 is greater than S8F1, we must utilize a beam whose thickness is 6 cm higher than S8F1 in order to be more cost-effective. Table 4 shown the beam specimens used as layers with Reference beam N.C, S8F0 and S8F1
Keywords: Silica Fume; steel fiber Compressive Strength; stiffnes; ductility